2003
DOI: 10.1134/1.1618992
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the interaction between the stream and cool accretion disk in a semidetached binary system

Abstract: We analyze heating and cooling processes in accretion disks in binaries. For realistic parameters of the accretion disks in close binaries (• M ≃ 10 −12 ÷ 10 −7 M ⊙ /year and α ≃ 10 −1 ÷ 10 −2 ), the gas temperature in the outer parts of the disk is ∼ 10 4 K to ∼ 10 6 K. Our previous gas-dynamical studies of mass transfer in close binaries indicate that, for hot disks (with temperatures for the outer parts of the disk of several hundred thousand K), the interaction between the stream from the inner Lagrange po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(80 citation statements)
references
References 19 publications
4
76
0
Order By: Relevance
“…This raises the question of what leads to the presence of matter at considerable heights above the accretion disk in the case of a stationary interaction between the stream and the disk. Gasdynamical studies of the terminal flow pattern in semi-detached binaries demonstrate that the interaction between the stream and the disk is collisionless in this case [18][19][20][21][22][23][24]. In contrast to the hot-spot model, which assumes that the stream impacts the edge of the accretion disk, the stream interacts with gas of the circumdisk halo in the stationary case, forming an extended region of enhanced energy release, or so called "hot line".…”
Section: Introductionmentioning
confidence: 99%
“…This raises the question of what leads to the presence of matter at considerable heights above the accretion disk in the case of a stationary interaction between the stream and the disk. Gasdynamical studies of the terminal flow pattern in semi-detached binaries demonstrate that the interaction between the stream and the disk is collisionless in this case [18][19][20][21][22][23][24]. In contrast to the hot-spot model, which assumes that the stream impacts the edge of the accretion disk, the stream interacts with gas of the circumdisk halo in the stationary case, forming an extended region of enhanced energy release, or so called "hot line".…”
Section: Introductionmentioning
confidence: 99%
“…Matter can also be transported into the circumbinary space via a wind/outflow from the accretion disk or the secondary star as a natural consequence of the mass transfer. Numerical simulations of the mass transfer process in CVs have demonstrated that as much as 50% of the transferred matter can escape from the WD's Roche lobe and end up in the circumbinary space around the CV (Bisikalo et al 2003;Bisikalo & Kononov 2010). Infrared observations of CVs by the Spitzer Space Telescope have revealed the presence of dust in many systems, indicating the possible origin of a CB disk (Howell et al 2006;Dubus et al 2007;Hoard et al 2007Hoard et al , 2009.…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation in the model, of extended spots at the disk outer rim, follows results of hydrodynamical simulations of gas dynamics in interacting close binary stars showing similar structures (e.g. Bisikalo et al 2003), as explained in detail in the next section.…”
Section: The Fitting Proceduresmentioning
confidence: 99%
“…The hot and bright spots might be tentatively identified with shock regions, characterized by higher density and higher temperature than the surrounding medium, revealed in hydrodynamical simulations of mass transfer in close binaries by Bisikalo et al (1998Bisikalo et al ( , 1999Bisikalo et al ( , 2003. In particular, the hot spot is near the place where a ballistic trajectory of a particle released in the inner Lagrangian point intersects the accretion disc.…”
Section: The Best Light-curve Modelmentioning
confidence: 99%
See 1 more Smart Citation